Treatment with cyclic adenosine monophosphate modulators prior to in vitro maturation alters the lipid composition and transcript profile of bovine cumulus-oocyte complexes and blastocysts - Razza, Eduardo M.; Sudano, Mateus J.; Fontes, Patricia K.; Franchi, Fernanda F.; Belaz, Katia Roberta A.; Santos, Priscila H.; Castilho, Anthony C. S.; Rocha, Daniele F. O.; Eberlin, Marcos N.; Machado, Mariana F.; Nogueira, Marcelo F. G. (CSIRO Publishing, 2018)
Mammalian oocytes resume meiosis spontaneously after removal from the ovarian follicle. We tested the effects of a 2-h prematuration treatment (Pre-IVM) with forskolin (FSK) and 3-isobutyl-1-methylxanthine (IBMX) in bovine cumulus-oocyte complexes (COCs) on the lipid content of oocytes and blastocysts, on the membrane lipid composition of blastocysts and on the transcriptional profiling of cumulus cells and blastocysts in a high-throughput platform. Embryonic development rates to the morula (mean 56.1%) or blastocyst (mean 26.3%) stages were unaffected by treatment. Lipid content was not affected after Pre-IVM, but was increased after IVM in treated oocytes. Conversely, the lipid content was reduced in Pre-IVM blastocysts. Pre-IVM COCs generated blastocysts containing blastomeres with more unsaturated lipids in their membranes. Pre-IVM also altered the relative abundance of 31 gene transcripts after 2 h and 16 transcripts after 24 h in cumulus cells, while seven transcripts were altered in blastocysts. Our results suggest that the Pre-IVM treatment affected the lipid composition and transcriptional profiles of COCs and blastocysts. Therefore, Pre-IVM with FSK and IBMX could be used either to prevent spontaneous meiotic resumption during IVM or to modulate lipid composition in the membrane and cytoplasm of blastocysts, potentially improving bovine embryos.
Keywords: cAMP; gene expression; mass spectrometry